2020
DOI: 10.15376/biores.15.4.ethaib
|View full text |Cite
|
Sign up to set email alerts
|

Toward sustainable processes of pretreatment technologies of lignocellulosic biomass for enzymatic production of biofuels and chemicals: A review

Abstract: Lignocellulosic biomass is a class of sustainable material that can be utilized as a raw feedstock in biofuel and chemical production. However, the complex matrix structure of lignocellulosic materials complicates conversion processes, such as enzymatic hydrolysis. Therefore, an efficient pretreatment process is required to disrupt the plant cell wall structure and maximize the recovery of valuable soluble components from lignocellulosic biomass during hydrolysis. In addition, an effective pretreatment method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“… 28 So there is a need to develop a pretreatment processes which reduce the energy requirement as well minimize the production of inhibitors during the processes of pretreatment. 29 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 So there is a need to develop a pretreatment processes which reduce the energy requirement as well minimize the production of inhibitors during the processes of pretreatment. 29 …”
Section: Introductionmentioning
confidence: 99%
“…28 So there is a need to develop a pretreatment processes which reduce the energy requirement as well minimize the production of inhibitors during the processes of pretreatment. 29 Clostridium clariavum is anaerobic, Gram-positive, rod shaped, non-motile, moderately thermophilic, cellulose degrading, and chemo-organotrophic bacterium. 30,31 The sequence of C. clariavum revealed that its genome carries different genes that encode cellulosomal proteins as well as polysaccharide-degrading enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of degradation of structural polysaccharides depends on the process parameters of the microwave-assisted pretreatment. The main factors deciding about the concentration of sugars in hydrolysates include the type of reagent and time 26 , 27 . The effectiveness of the use of microwave radiation in lignocellulosic biomass pretreatment was confirmed for food industry waste, cereal straw, distillery stillages, and exotic plant biomass 28 32 .…”
Section: Introductionmentioning
confidence: 99%
“…[8] However, there are still some aspects such as low lignin removal and inhibitors generation at harsh SE conditions should be considered, which hinder the subsequent costeffective enzymatic saccharification process. [9] To reduce the severity of explosion (e. g., lowering temperature and pressure, shortening residence time) and maximize the recovery of valuable components, some chemical additives, mainly mineral acids or alkalis (e. g., SO 2 , H 2 SO 4 , H 3 PO 4 , and NH 4 ) are introduced. [10] Dilute phosphoric acid plus steam explosion (DPASE) is a promising alternative LCB pretreatment method, [11] holding advantages as follows: (i) acting as an exogenous weak acid catalyst, dilute H 3 PO 4 results in low sugar loss and toxins yield simultaneous with explosion; [12] (ii) H 3 PO 4 can not only serve as an additional source of nutrients for microbe, [13] but also partly be recovered and reused as fertilizer; [14] and (iii) H 3 PO 4 is less corrosive to explosion apparatus, which is beneficial for devices scaling up.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, steam explosion (SE) is of advantages such as time and energy saving, cost‐effective and environmentally‐ friendly LCB deconstruction, which is widely applied for hardwood and agricultural residue pretreatment [8] . However, there are still some aspects such as low lignin removal and inhibitors generation at harsh SE conditions should be considered, which hinder the subsequent cost‐effective enzymatic saccharification process [9] . To reduce the severity of explosion (e. g., lowering temperature and pressure, shortening residence time) and maximize the recovery of valuable components, some chemical additives, mainly mineral acids or alkalis (e. g., SO 2 , H 2 SO 4 , H 3 PO 4 , and NH 4 ) are introduced [10]…”
Section: Introductionmentioning
confidence: 99%